International Postgraduates’ Involvement in English Storytelling Volunteer Project for Taiwanese Children - Chieh-Lan , Li; Ali, Zuraidah (Management Analytics and Social Insights, 2026)
English is considered a foreign language in Taiwan; however, there is a growing emphasis on achieving English proficiency. Parents are increasingly enrolling their children in English tuition and enrichment programs, and even public libraries have introduced English-based weekend activities, including interactive community programs such as English storytelling sessions. Organizers of these activities often invite international university students to volunteer, fostering an immersive English-learning environment for children. In line with this trend, the Office of International Affairs at Ming Chi University of Technology (MCUT) engages postgraduate international students as volunteers to support English enrichment initiatives at nearby public libraries. Nevertheless, the rigorous academic demands of postgraduate studies present challenges for volunteer recruitment and retention. This study aims to explore the motivations of international postgraduate students to volunteer in helping Taiwanese children learn English. Twelve volunteers from diverse national backgrounds participated in the study. Semi-structured interviews were conducted, and the data were thematically analyzed, resulting in the identification of five key motivational themes. The findings offer insights into strategies for improving the recruitment, engagement, and retention of volunteers for English storytelling programs involving postgraduate students.